Understanding the determinants of the complex interplay between cost-effectiveness and equitable impact in maternal and child mortality reduction - Mickey Chopra; Harry Campbell; Igor Rudan (Edinburgh University Global Health Society, 2012)
One of the most unexpected outcomes arising from the efforts towards maternal and child mortality reduction is that all too often the objective success has been coupled with increased inequity in the population. The aim of this study is to analyze the determinants of the complex interplay between cost-effectiveness and equity and suggest strategies that will promote an impact on mortality that reduce population child health inequities.